2012
DOI: 10.1016/j.jas.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Stature and frailty during the Black Death: the effect of stature on risks of epidemic mortality in London, A.D. 1348–1350

Abstract: Recent research has shown that preexisting health condition affected an individual’s risk of dying during the 14th-century Black Death. However, a previous study of the effect of adult stature on risk of mortality during the epidemic failed to find a relationship between the two; this result is perhaps surprising given the well-documented inverse association between stature and mortality in human populations. We suggest that the previous study used an analytical approach that was more complex than was necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 50 publications
3
76
0
2
Order By: Relevance
“…Similarly, it has been shown that epidemic mortality in historic populations was apparently not selective with respect to age and sex among adults [8][9][10][11][12]. Conversely, it was shown that mortality associated with the medieval epidemic was selective with respect to frailty [10,11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been shown that epidemic mortality in historic populations was apparently not selective with respect to age and sex among adults [8][9][10][11][12]. Conversely, it was shown that mortality associated with the medieval epidemic was selective with respect to frailty [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, it was shown that mortality associated with the medieval epidemic was selective with respect to frailty [10,11]. Individuals who were in poor health before the epidemics were more likely to die than were their healthy peers [11].…”
Section: Methodsmentioning
confidence: 99%
“…These findings were interpreted within the broader sphere of adaptive plasticity and constraint as faster maturation likely permitted earlier reproduction, but this process was associated with elevated mortality. The impact of early life stress on survivorship in the wake of infectious disease epidemics is also illustrated in historic cemeteries used as repositories for victims of bubonic plague . Individuals with shorter stature had a greater risk of dying from the bubonic plague in historic London, although this association is not repeated under conditions of normal mortality.…”
Section: Bioarchaeological Approachesmentioning
confidence: 99%
“…Results of hazard modeling demonstrate that elevated mortality rates were commonplace during the latter half of the Mississippian period (AD 1200-1450) with reproductive-age females experiencing high age-specific risk of death attributed to the development of fortified villages and novel environments for increased pathogen loads. While scholars continue to reference this paradox and ponder the theoretical implications (e.g., Goodman and Martin, 2002;Lambert, 2009), the methodological challenges associated with analyzing death assemblages have been largely overlooked with several notable exceptions (Boldsen, 1997(Boldsen, , 2005(Boldsen, , 2007Usher, 2000;DeWitte and Wood, 2008;DeWitte, 2010;Bekvalac, 2010, 2011;Redfern and DeWitte, 2011;DeWitte and Hughes-Morey, 2012;DeWitte et al, 2013). The epidemiological models demonstrate that the relationship between adult mortality and early childhood stress varied through space, culture, and time.…”
mentioning
confidence: 99%